Kebijakan Pendanaan Versus Ukuran Perusahaan Dalam Perolehan Return Saham yang Positif - Ana Kadarningsih; Anita Nur Utomo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
Share value is a benchmark for investors to see the success of a company. A positive stock return (capital gain) is a benchmark for companies for business success. This study has three objectives, namely how to influence funding policy on stock returns, to find out the relationship between the size of the company and the size of the company to stock returns, and finally to see how far the liquidity relat ionship affects stock returns. The total population in this study were 67 companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange for the 2015-2017 period. Purposive sampling technique was used to obtain samples according to the criteria. The samples collected according to the criteria were 55 companies with 165 data processed. The research analysis method uses multiple linear regression analysis with the addition of statistical descriptive tests, normality tests, coefficient of determination tests. The analysis tool used SPSS version 21. The results showed that only one variable did not affect stock returns, namely liquidity. Two other variables, namely funding policy and company size significantly affect stock returns but in different directions. Funding policy has a negative effect, while company size has a positive effect on stock returns.